RANCANG BANGUN MODEL PENGENDALIAN DANA OPERASIONAL PENDIDIKAN (BOP) PENDIDIKAN ANAK USIA DINI (PAUD) DENGAN PENDEKATAN SOFT SYSTEM METHODOLOGY PADA DINAS PENDIDIKAN KABUPATEN LAMPUNG SELATAN - Agus Purnomo; Yeli Erika (e-JKPP, 2019)
Public problems are problems that concern the interests of many people which are very crucial to be handled by the government, so that they require serious and alternative handling to solve these public problems. One of the public problems that require serious handling is the problem of education. Every child has the right to education and teaching in the context of personal development and the level of intelligence according to their interests and talents. Early childhood education has an important meaning for the future of children in helping to apply good knowledge and discipline in early childhood, as well as assisting the development of children's character through the process of understanding children's character and social skills with their surroundings. To support the operational activities of education, the government provides Operational Assistance for the Implementation of Early Childhood Education which functions to improve quality education services.Based on the formulation of the problem above, the aim of this study is "Design of Education Operational Fund Control Model for Early Childhood Education with Soft System Methodology Approach in the Education Office of South Lampung Regency". The conclusions obtained from this study are (1) The process of controlling at the South Lampung Regency Education Office starts from requests for assistance to reporting the use of through a long, convoluted and ineffective process. (2) There are still some institutional operators who are not yet skilled in dapodic data processing, proposal preparation and accountability reporting, thus delaying the submission process to reporting the use of funds. (3) Lack of facilities and infrastructure in most institutions, such as computers and internet connections, which affect the delivery of Dapodic Data to the Ministry of Education is slow. (4) The slow completion of the is because all institutions must be present in the process of signing to the Education Office and the delay in the verification process by officials at the Education Office which is deemed ineffective. (5) With the model development process it is expected that the control at the South Lampung District Education Office will be 4 weeks, while the 6 (six) stages (real condition) system has a length of service time of up to 7 weeks, so that the ontrol process becomes faster and more effectiveBased on the formulation of the problem above, the aim of this study is "Designing a Model of Operational Fund Control for Early Childhood Education with Soft System Methodology Approach in the Education Office of South Lampung Regency". The conclusions obtained from this study are (1) The control process at the South Lampung District Education Office, starting from requests for assistance to reporting on its use, is a long, convoluted and ineffective process. (2) There are still some institutional operators who are not yet skilled in dapodic data processing, proposal making and accountability reporting, thus slowing down the submission process to reporting the use of funds. (3) Lack of facilities and infrastructure in most institutions, such as computers and internet connections, which affect the delivery of Dapodic Data to the Ministry of Education is slow. (4) The slow completion of cooperation is due to the fact that all institutions must be present in the process of signing the collaboration to the Education Office and the delay in the verification process by officials at the Education Office who are deemed ineffective. (5) With the model development process, it is expected that the control at the South Lampung Regency Education Office will be 4 weeks, while the 6 (six) stage (real condition) system takes 7 weeks of service time, so that the control process becomes faster and more effective.